Pocket book on knowledge and perception of stunting among public health cadre in Indonesia - Sugeng Santoso; Rinayati Rinayati; Harsono Harsono; Eman Dawood (Malahayati International Journal of Nursing and Health Science, 2025)
Background: As many as 24 million children in Indonesia are at risk of malnutrition. Equipped with training using appropriate media and opportunities, interacting with early childhood education teachers and parents, health cadres are expected to be able to detect stunting early and provide counseling to parents. Meanwhile, health cadres have never received material on early detection and prevention of stunting. Purpose: To determine the effectiveness of a stunting pocketbook developed for health cadres. Method: Quantitative research using a survey of 36 health cadres selected randomly in Ngaliyan District. The study population was all health cadres in Ngaliyan District, with a sample of 36 teachers determined by total sampling. Data analysis used univariate analysis with frequency distribution and the Wilcoxon Signed Rank test. Results: There was a difference in the average knowledge of health cadres after using the stunting pocketbook (p-value: 0.000). Conclusion: The stunting pocketbook can be used by health cadres as a medium for providing counseling to parents to reduce the prevalence of stunting in Indonesia.